Hydrocortisone Cream to Reduce Perineal Pain after Vaginal Birth. Issue 5 (September 2015) - Manfre, Margaret; Adams, Donita; Callahan, Gloria; Gould, Patricia; Lang, Susan; McCubbins, Holly; Mintz, Amy; Williams, Sommer; Bishard, Mark; Dempsey, Amy; Chulay, Marianne
Abstract Purpose: To determine if the use of hydrocortisone cream decreases perineal pain in the immediate postpartum period. Study Design and Methods: This was a randomized controlled trial (RCT), crossover study design, with each participant serving as their own control. Participants received three different methods for perineal pain management at three sequential perineal pain treatments after birth: two topical creams (corticosteroid; placebo) and a control treatment (no cream application). Treatment order was randomly assigned, with participants and investigators blinded to cream type. The primary dependent variable was the change in perineal pain levels (posttest minus pretest pain levels) immediately before and 30 to 60 minutes after perineal pain treatments. Data were analyzed with analysis of variance, with p < 0.05 considered significant. Results: A total of 27 participants completed all three perineal pain treatments over a 12-hour period. A reduction in pain was found after application of both the topical creams, with average perineal pain change scores of -4.8 ± 8.4 mm after treatment with hydrocortisone cream (N = 27) and -6.7 ± 13.0 mm after treatment with the placebo cream (N = 27). Changes in pain scores with no cream application were 1.2 ± 10.5 mm (N = 27). Analysis of variance found a significant difference between treatment groups (F2, 89 = 3.6, p = 0.03), with both cream treatments having significantly better pain reduction than the control, no cream treatment (hydrocortisone vs. no cream, p = 0.04; placebo cream vs. no cream, p = 0.01). There were no differences in perineal pain reduction between the two cream treatments (p = .54). Clinical Implications: This RCT found that the application of either hydrocortisone cream or placebo cream provided significantly better pain relief than no cream application.